2014
DOI: 10.1186/1746-1596-9-94
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of insulin/IGFs pathways by sirtuin-7 inhibition in drug-induced chemoreistance

Abstract: BackgroundInsulin and insulin-like growth factors (IGFs) are key regulators of metabolism and growth. Recent evidences suggest a key role of these pathways in non-classical tissues and the metabolic pathways by which these hormones exert their effects in neoplasia is unclear.AimsTo study insulin/IGFs pathways in drug sensitive and resistant cancer cells representing breast cancer (MCF-7), osteosarcoma (SaOS-2), and ovarian cancer (A2780) and to examine the effect of Sirtuin-7 (Sirt7) inhibition on insulin/IGFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Curiously, the sirtuins whose expression decreases in the ApoD-KO aged brain are not directly related to lifespan extension. Loss-of-function manipulations have related them to premature cellular senescence (Sirt7, Aljada et al, 2014) or stress induced genomic instability (Sirt4, Jeong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, the sirtuins whose expression decreases in the ApoD-KO aged brain are not directly related to lifespan extension. Loss-of-function manipulations have related them to premature cellular senescence (Sirt7, Aljada et al, 2014) or stress induced genomic instability (Sirt4, Jeong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…McGlynn et al demonstrated that decreased SIRT7 expression is associ-ated with an aggressive tumor phenotype and poor survival (38). SIRT7 knockdown also induces multidrug resistance in breast cancer cells (39). miRNAs represent novel inhibitors for gene expression (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT7 knockdown downregulated pol III activity to decrease tRNA syntheis and subsequently protein synthesis [27]. A connection between SIRT7 and insulin/IGF-1 signalling pathways has also emerged [28]. Using SIRT7 knockout mice two contradictiory roles of SIRT7 have been reported with respect to lipid metabolism [23,29].…”
Section: Introductionmentioning
confidence: 97%